Assessment of pre‐operative maropitant citrate use in macaque (Macaca fasicularis & Macaca mulatta) neurosurgical procedures. Issue 3 (2nd April 2018) - Steinbach, Jaclyn R.; MacGuire, Jamus; Chang, Shu; Dierks, Elizabeth; Roble, Gordon S.
Abstract: Background: Retrospective analysis of post‐operative vomiting (POV) in non‐human primates at our institution was 11%. Based on this additional risk factor for post‐operative complications, we aimed to eliminate or decrease POV by adding an antiemetic, maropitant citrate, to the pre‐medication protocol. Methods: Retrospective and prospective data were collected over a 5‐year period from 46 macaques of two species during 155 procedures. Additionally, blood was collected from five Macaca mulatta to perform a pharmacokinetic analysis. Results: A 1 mg/kg subcutaneous dose of maropitant given pre‐operatively significantly decreased POV. Findings indicated post‐neurosurgical emesis in Macaca fasicularis was significantly greater than in Macaca mulatta . Pharmacokinetic analysis of maropitant in Macaca mulatta determined the mean maximum plasma concentration to be 113 ng/mL. Conclusions: Maropitant administration prior to anesthesia for neurosurgeries decreased our incidence of POV to 1%. The plasma concentration reaches the proposed plasma level for clinical efficacy approximately 20 minutes after administration.